Morphological features of indigenous chicken populations of Ethiopia - Dana, N.; Dessie, Tadelle; Waaij, E.H. van der; Arendonk, Johan A.M. van (Cambridge University Press, 2010)
This study describes the variations in the physical features and the useful attributes of different populations of indigenous chickens. Five populations of chickens in different regions of Ethiopia were studied based on 13 qualitative traits recorded for a total of 1 125 chickens. Additional measurements on quantitative traits (shank length and body weight) were also included. Descriptive statistics (nonparametric and F tests) were used to analyze the data. Each of the study populations possessed multiple variants of plumage colours and other physical features. However, white body plumage is one of the prominent features of Farta chickens and red is predominant in the other populations. Pea comb is the dominant comb type in all regions. Most of the chickens in the high altitude regions have yellow skin. The geographic distribution and frequency of naked neck chickens are generally small, and the available small proportion is found mainly in the low altitude regions. Males in all populations are heavier and taller than the females. Body weights range from 1 411 g (Konso) to 1 700 g (Horro) in adult males and from 1 011 g (Konso) to 1 517 g (Sheka) in females. Most of the morphological traits that were studied showed a very low level of associations with each other.